Mental health education in occupational therapy professional preparation programs: Alignment between clinician priorities and coverage in university curricula. (29th June 2017) - Scanlan, Justin Newton; Meredith, Pamela J.; Haracz, Kirsti; Ennals, Priscilla; Pépin, Geneviève; Webster, Jayne S.; Arblaster, Karen; Wright, Shelley
Abstract : Background/aim: Occupational therapy programs must prepare graduates for work in mental health. However, this area of practice is complex and rapidly changing. This study explored the alignment between educational priorities identified by occupational therapists practising in mental health and level of coverage of these topics in occupational therapy programs in Australia and New Zealand. Methods: Surveys were distributed to heads of all occupational therapy programs across Australia and New Zealand. The survey included educational priorities identified by occupational therapists in mental health from a previous study. Respondents were requested to identify the level of coverage given to each of these priorities within their curriculum. These data were analysed to determine a ranking of educational topics in terms of level of coverage in university programs. Results: Responses were received for 19 programs from 16 universities. Thirty‐four topics were given 'High‐level coverage' in university programs, and these were compared against the 29 topics classified as 'Essential priorities' by clinicians. Twenty topics were included in both the 'Essential priorities' and 'High‐level coverage' categories. Topics considered to be 'Essential priorities' by clinicians which were not given 'High‐level coverage' in university programs included the following: mental health fieldwork experiences; risk assessment and management; professional self‐care resilience and sensory approaches. Conclusion: While there appears to be overall good alignment between mental health curricula and priorities identified by practising occupational therapists, there are some discrepancies. These discrepancies are described and establish a strong foundation for further discussion between clinicians, academics and university administration to support curriculum review and revision.